Backscatter communication assisted vehicular positioning technology with ultra-high accuracy - Kaifeng HAN; Tiezhi LIU (Dianxin kexue)
The accurate vehicular positioning technology has been the fundamentalfunction for safer auto-driving and vehicular-to-everything networks.One research trend focuses on enabling the low-cost,reliable,and accurate vehicular positioning in high-density cities,tunnels,and underground where the GPS or cellular positioning can’t work due to the signaling blocking.To this end,a novel backscatter communication assisted vehicular positioning system was proposed where a backscatter-reader (with two antennas) was deployed on vehicle and at least one backscatter-tag is deployed along a roadside,based on which the location of vehicle could be estimated with ultra-high reliability and accuracy.Through simulation verification,BackCom vehicle positioning technology can achieve extremely high positioning accuracy.At the same time,BackCom’s vehicle positioning technology is very easy to expand.By increasing the number of antennas in its positioning reader,it could further improve its positioning accuracy.BackCom vehicle positioning technology has the advantages of low cost,low power consumption,high accuracy,high reliability,and easy deployment.It is suitable for various driving environments and has extremely high theoretical research value and commercial value.